A Brief Overview of Bacteriocins and their Potential Applications against Phytopathogenic Bacteria - Maurya , Shivam; Kaur , Gurpreet; Kumar , Chandan; Sahani , Shrawan Kumar; Sharma , Shashikant; Rehan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Gram-negative phytopathogens severely harm a number of economically significant crop plants. The effectivity of traditional approaches, such as the breeding and introduction of resistant cultivars, is limited by the lack of available sources of genetic resistance. Bacteriocins are small proteinaceous antibiotics produced by bacteria to kill closely related bacteria. Utilization of narrow-spectrum protein antibiotics as biocontrol agents is an effective strategy to shrink losses imposed due to specific bacterial phytopathogens. Several colicin-like bacteriocins have been found to be active against phytopathogenic bacteria. Bacteriocins frequently affect closely related bacterial strains, making them useful as targeted, low-side-effect, narrow-spectrum antibiotics. Even though using bacteriocins to control plant diseases is a promising strategy, minimal information is there regarding the abundance and functions of these chemicals against pathogenic bacteria and their natural enemies. This review is concerned with the efficient control of economically significant plant pathogenic bacteria using these potent and selective antimicrobial agents.